ALTERNATIVE MARKETING STRATEGIES FOR LOW SEASON PERIOD AT COURTYARD BY MARRIOTT BALI SEMINYAK RESORT - Ni Putu Lusiana Pratiwi; Made Sudiarta (Politeknik Negeri Bali, 2019)
This study was conducted to determine the company's strategy in raising hotel revenue during the low season. The purpose of this research is to find out the prioritized marketing strategies during the low season. The research method of this study is a combined qualitative and quantitative method. The key respondents of 6 staffs including managers in the Sales and Marketing Department. The data analysis techniques used are Internal Factor Analysis Summary (IFAS) and External Factor Analysis Summary (EFAS), Internal-External (IE) Matrix, SWOT Analysis, and Quantitative Strategic Planning Matrix (QSPM) Analysis. The results showed that the hotel's internal and external factors were influential in increasing revenues. Based on the IFAS matrix, the main strength of the hotel is the service by prioritizing the quality of the restaurant and Spa at the hotel, the downside is not having direct access to the beach. In the EFAS matrix, it is known that one of its chances is very good internet speed and can be reached until the basement; the threat is many competitors offer cheaper room rates. The result of the IE Matrix Assessment puts the company in the position of Growth cell I (Concentration through Vertical Integration). SWOT analysis has resulted in 8 alternative marketing strategies. The main strategy with a value of TAS (Total Attractive Score) of 158.80 resulted from QSPM analysis is expanding restaurant and spa promotion through social media.